Republic of Serbia : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This staff report on the Republic of Serbia's Article IV Consultation highlights economic background and policies. The global financial crisis exposed Serbia's unsustainable growth model and its key vulnerabilities. Robust growth has not taken off, and economic activity is below precrisis levels amid widespread structural rigidities. Serbia's economy is recovering from recession but faces multiple challenges. The successful launch of Fiat production in 2012 is contributing to growth this year, and inflation is declining. Potential growth is constrained by multiple structural hurdles resulting from unfinished structural reforms. Rebalancing the policy mix and launching a comprehensive package of structural reforms are critical to unlocking Serbia's growth potential.